Coaching Strategies to Improve Religious Understanding For Muallaf - Tasbih Tasbih; Siti Asiqah Usman Ali; Saidah A.H Saidah A.H (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2022)
This study aims to explore coaching strategies to improve religious understanding for muallaf. The research uses qualitative techniques with main data collection techniques through FGDs, observations, interviews, and documentation. The research was conducted in Kampung Muallaf, Betteng Village, Lembang District, Pinrang Regency, South Sulawesi Province. The data are analyzed qualitatively using classification based on emerging problems. The results showed that the muallaf coaching strategy in Betteng Village was appropriate. Some of the steps taken are in physical form, and some are in non-physical form. The physical form is the manufacture of several facilities and infrastructure, while the nonphysical form is the form of deepening the pillars of faith and the pillars of Islam. The inhibiting factors for Kampung Muallaf in Betteng Village are the lack of Islamic extension personnel and extreme road access resulting in a lack of frequent meetings. Therefore,it is recommended that the government increase the energy of Islamic Extension workers and improve the means of transportation to make it easier to carry out guidance. The main contribution of this research is to be a piece of information about the concrete steps of religious formation. These measures can be used as a pilot in fostering muallaf elsewhere.